EVALUATION OF THE EFFICACY OF A LIPOSOMAL IRON PREPARATION FOR THE TREATMENT OF ANEMIC SYNDROME - Suleymanova D. N.; Ulugova Sh. T. (Modern American Journals, 2025)
Evaluation of the tolerability of the liposomal drug "Liposemi Plus" showed that 100% of patients assessed it as "good", side effects from the gastrointestinal tract typical of conventional oral iron preparations were detected in only 2.2% of patients. For patients with leukemia, it is especially important to protect the gastrointestinal tract from side effects of drugs, since constant chemotherapy already creates a serious negative load on the gastrointestinal tract.